Penerapan Standard Operating Procedure Room Service di Mandapa a Ritz-Carlton Reserve - Yudistira, I Gusti Ngurah Bagas; Astina, Made Arya; Hum, M. (Penerbit Goodwood, 2024)
Purpose: The purpose of this study is to find out what obstacles occur during Room Service services and to find out the implementation of the Standard Operating Procedure (SOP) at Mandapa A Ritz-Carlton Reserve.Research methodology: This study uses primary and secondary data through observation and interviews. Data was collected by observing 5 staff at In Villa Dining regarding the Standard Operating Procedure (SOP) at Mandapa A Ritz-Carlton Reserve.Results: Based on the observation results, there are two Standard Operating Procedures: Telephone Service Assistance (TSA) with 31 work instructions (29 always carried out, 2 not always), and Entering Guest's Villa with 16 work instructions (15 always carried out, 1 never carried out).Conclusions: This study concludes that there are two Standard Operating Procedures (SOPs) implemented in Room Service, namely SOP Telephone Service Assistance (TSA) and SOP Entering Guest's Villa. Most of the instructions in both SOPs have been carried out properly by the staff. However, there are some instructions that are not always or never carried out optimally due to situational conditions and guest preferences.Limitations: This study has limitations in the scope of observation which is limited to one specific time and place, so it cannot describe the application of SOPs as a whole in various operational conditions and different locations.Contributions: This research makes a real contribution in understanding the level of SOP implementation in Room Service and identifying obstacles faced in the field. The results of this study are expected to be input for hotel management in improving service quality through evaluation and improvement of SOPs that are more adaptive to the needs and situations in the field.Keywords: Hambatan, Penerapan, Room Service, Standard Operating Procedure (SOP).How to Cite: Yudistira, I. G. N. B., Astina, M. S., & Hum, M. (2024). Penerapan standar operating procedure room service di mandapa a Ritz-Cartlon Reserve. Jurnal studi perhotelan dan pariwisata, 2(2), 87-97.